Immersive awareness. Issue 2 (4th May 2018) - Middleton, Deborah; Núñez, Nicolás
Abstract : This article explores an approach to training for immersive theatre performance which addresses the need for an expanded and multi-focal awareness. Drawing on the Movements from Grotowski's Theatre of Sources period, Núñez's training process for El Ensueño de los Árboles (2017) is discussed in terms of meditation-in-movement and deconditioning of perception. This training is considered as a training in the capacity for immersion.